EFFECT OF POST THAW INCUBATION ON QUALITY OF FROZEN THARPARKAR BULL SEMEN - KEDIA, N K; TIWARl, R P; MISHRA, G K; AWASTHl, M K; SAHU, S B (The Indian Journal of Animal Reproduction, 2023)
The period spent after thawing and before insemination may affect the quality and fertility of post thawsemen. The frozen semen was thawed at 37°C for 30 seconds and taken into a small sugar tube and incubated inthe water bath at 37°C for 0, 15, 30, 45 and 60 min and post thaw motility (PTM % ), hypo osmotic swelling test(HOST%) and cervical mucus penetration test (CMPT -mm/60 min) were carried out. The mean (range) of PTMobserved at respective intervals was 52.22 ± 1.09 (45-60), 51.39 ± 0.97 (45-60), 46.94 ± 0.59 (45-50), 40.28 ± 0.85(35-45) and 32.22 ± 0.92 (25-40) %. The corresponding values of HOST were 54.39 ± 2.54 (30-71), 51.28 ± 1.79(40-65), 44.77 ± 1.87 (32-58), 34.17 ± 1.49 (23-43) and 24.50 ± 1.10 (16-32) % and CMPT 29.39 ± 1.16 (22-40),27.78 ± 0.92 (23-36), 23.11 ± 0.81 (19-31 ), 16.39 ± 0.16 (12-24) and 10.28 ± 0.54 (7-15) mm/60min. The overallpost thaw motility at 0, 15 and 30 min was found to. be significantly higher (P
Keywords: CMPT; HOST; Incubation period; PTM; Tharparkar bull semen